Regulating Pharmacy Practice: Analysis of Pharmacy Laws in Ten States - Alex J. Adams (University of Minnesota Libraries Publishing, 2020)
Background: The National Association of Boards of Pharmacy (NABP) recently established a task force to help states develop regulations based on "standards of care" rather than "prescriptive rule-based regulation." This signals a shift in orthodoxy as pharmacy has traditionally been a highly regulated profession. A benchmark report on the pharmacy, nursing, and medical statutes and regulations in Idaho found that pharmacy had a higher overall word count, more overall restrictions, and had to be amended more frequently to keep pace with change. Objective: To identify opportunities to make the transition to a "standard of care" regulatory model in pharmacy law, this manuscript attempts to quantify the regulatory burden for 10 Western U.S. states. Method: The relevant statutes and regulations were gathered from each of the 10 states, and key measures were extracted, including word count, restrictions, exemptions, and the composition. Results: States exhibited wide variation in overall regulatory burden as measured by word count (average of 65,882 words, SD=35,057). The top categories of pharmacy law are: 1) professional practice standards (25,249 ± 16,077 words); 2) facility standards (15,230 ± 10,240 words); and 3) licensing (11,412 ± 6,191 words). More than 65% of all pharmacy regulations are in rule adopted by board of pharmacy rather than in statutes passed by the legislature. Conclusions: States exhibited major variation in total regulatory burden, with the largest contributors to cross-state variation being regulations related to professional practice standards and facility standards. This analysis suggests these two areas should be the primary targets of states looking to decrease regulatory burdens and that regulatory boards have a significant opportunity to remove regulatory burdens even in the absence of legislative action.